2013
DOI: 10.1038/jhh.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the angiotensin II receptor antagonist olmesartan on morning home blood pressure in hypertension: HONEST Study at 16 weeks

Abstract: Morning home blood pressure (BP) levels are more closely associated with cardiovascular risk than clinic BP levels. However, control of morning home BP has been worse than that of clinic BP in clinical practice. We examined the effects of olmesartan-based treatment using data (n=21 341) from the first 16 weeks of the Home BP measurement with Olmesartan Naive patients to Establish Standard Target blood pressure (HONEST) study, a prospective observational study for olmesartan-naive patients with essential hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
(49 reference statements)
0
19
0
2
Order By: Relevance
“…8 In our previous article describing the findings of the HONEST study, we reported a decrease in the proportion of patients with poorly controlled hypertension (PCH), that is, patients whose HBP and CBP were both high, and a consequent increase in the proportion of patients with WCH or MH after treatment with olmesartan. 9 After 16 weeks, the numbers of patients in both the WCH group and the MH group were approximately double the numbers at baseline. 9, 10 …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…8 In our previous article describing the findings of the HONEST study, we reported a decrease in the proportion of patients with poorly controlled hypertension (PCH), that is, patients whose HBP and CBP were both high, and a consequent increase in the proportion of patients with WCH or MH after treatment with olmesartan. 9 After 16 weeks, the numbers of patients in both the WCH group and the MH group were approximately double the numbers at baseline. 9, 10 …”
Section: Introductionmentioning
confidence: 92%
“…9 After 16 weeks, the numbers of patients in both the WCH group and the MH group were approximately double the numbers at baseline. 9, 10 …”
Section: Introductionmentioning
confidence: 92%
“…В исследовании HONEST олмесартана у наивных пациентов с артериальной гипертензией особое внимание уделялось отношению АД на визите к врачу и при самостоятельном измерении. Kario et al (2013) были проанализированы данные 21341 пациента в проспективном наблюдении на протяже-нии 16 недель. Пациенты контролировали АД само-стоятельно по утрам и во время визитов к врачу.…”
Section: Problems In Pharmacotherapy Of Resistant Arterial Hypertensionunclassified
“…Эти данные, по мнению авторов, не только свидетельствуют об эффективно-сти олмесартана, но и обращают внимание на важ-ность разностороннего контроля АД, так как при лечении и нормализации АД происходит повыше-ние частоты гипертензии "белого халата", что может сказываться на общем качестве лечения. Авторы подчёркивают, что "в реальном мире" олмесартан способствует эффективному контролю АД, в том числе, при сахарном диабете и хронической болезни почек [20].…”
Section: Problems In Pharmacotherapy Of Resistant Arterial Hypertensionunclassified
“…According to the available literature only one small sample size study of CPAP effects on the prevalence of MH has been published 15 . Kario et al 23 considered masked hypertension as a first step toward correct blood pressure compensation. If we assume that CPAP improves blood pressure, it should also reduce masked hypertension.…”
Section: Introductionmentioning
confidence: 99%